The efficacies and biomarker investigations of antiangiogenic agents and PD-1 inhibitors for metastatic soft tissue sarcoma: A multicenter retrospective study - Liu, Zhiyong; Wang, Xin; Wang, Jiaqiang; Zhang, Peng; Li, Chao; Wang, Bangmin; Gao, Songtao; Liu, Oufei; Yao, Weitao (Frontiers in Oncology, 2023)
Objective: To investigate the efficacy and safety of antiangiogenesis-immunotherapy therapy in patients with advanced STS in China, and to explore the potential factors of prognosis. Patients and Methods: This retrospective study was conducted at three hospitals in China, and the patients with metastatic STS who were ineligible for or declined anthracycline-based chemotherapy received antiangiogenic agents (anlotinib or apatinib) plus programmed death-1 (PD‐1) inhibitors (camrelizumab or sintilimab) between June 2019 and May 2022. The primary endpoint was progression-free survival rate at 6 months (6-month PFSR), and the secondary endpoints were objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) and toxicity. Biomarkers that might affect the prognosis were explored. Results: Thirty-nine patients were included: 5 patients with alveolar soft tissue sarcoma (ASPS) and 34 with non-ASPS. With a median follow-up of 18.2 months, the 6-month PFSR was 51.3%, with the ORR of 20.5% and DCR of 76.9%, The median PFS and OS were 7.0 months and 17.2 months. The 6-month PFSR for patients with ASPS and non-ASPS was 80.0% and 47.1%, respectively. The most common adverse events were hypothyroidism (56.4%), followed by fatigue (46.2%), and hypertriglyceridemia (43.6%). No treatment-related deaths were observed. Patients with low baseline NLR (NLR < 4) had better 6-month PFSR than those with high NLR (NLR ≥ 4) (82.4% vs. 31.6%). Conclusion: Antiangiogenic agents plus PD-1 inhibitors showed acceptable toxicity and promising efficacy in patients with advanced STS, especially patients with ASPS, and a low NLR might serve as a reliable biomarker for 6-month PFSR, PFS, and OS. It provides a reference for randomized controlled trials.